High Risk First Degree Relatives of Type 1 Diabetics: An Association with Increases in CXCR3+ T Memory Cells Reflecting an Enhanced Activity of Th1 Autoimmune Response. (20th March 2014) - Milicic, Tanja; Jotic, Aleksandra; Markovic, Ivanka; Lalic, Katarina; Jeremic, Veljko; Lukic, Ljiljana; Rajkovic, Natasa; Popadic, Dušan; Macesic, Marija; Seferovic, Jelena P.; Aleksic, Sandra; Stanarcic, Jelena; et al.
Abstract : We analyzed the level of (a) CXCR3 + (Th1) and CCR4 + (Th2) T memory cells (b) interferon- γ inducible chemokine (IP-10)(Th1) and thymus and activation-regulated chemokine (TARC)(Th2), in 51 first degree relatives (FDRs) of type 1 diabetics (T1D) (17 high risk FDRs (GADA +, IA-2 + ) and 34 low risk FDRs (GADA −, IA-2 − )), 24 recent-onset T1D (R-T1D), and 18 healthy subjects. T memory subsets were analyzed by using four-color immunofluorescence staining and flowcytometry. IP-10 and TARC were determined by ELISA. High risk FDRs showed higher levels of CXCR3 + and lower level of CCR4 + T memory cells compared to low risk FDRs (64.98 ± 5.19 versus 42.13 ± 11.11; 29.46 ± 2.83 versus 41.90 ± 8.58%, resp., P < 0.001 ). Simultaneously, both IP-10 and TARC levels were increased in high risk versus low risk FDRs (160.12 ± 73.40 versus 105.39 ± 71.30; 438.83 ± 120.62 versus 312.04 ± 151.14 pg/mL, P < 0.05 ). Binary logistic regression analysis identified the level of CXCR3 + T memory cells as predictors for high risk FDRs, together with high levels of IP-10. The results imply that, in FDRs, the risk for T1D might be strongly influenced by enhanced activity of Th1 and diminished activity of Th2 autoimmune response.